Review of Hyllus C.L. Koch, 1846 in Vietnam, with descriptions of three new species (Araneae: Salticidae) - Quang D. Hoang (European Journal of Taxonomy)
The jumping spider genus Hyllus C.L. Koch, 1846 in Vietnam is reviewed, including descriptions of three new species: H. taysonensis sp. nov. (♂♀), H. vietnamensis sp. nov. (♂♀), and H. zabkai sp. nov. (♀). The species H. diardi (Walckenaer, 1837), originally described from southern Vietnam, is redescribed from both sexes. Specimens from northeastern Vietnam previously misidentified as H. diardi are assigned to H. vietnamensis sp. nov. The species name Phidippus tirapensis Biswas & Biswas, 2006 is removed from the synonymy with H. diardi and transferred to the genus Hyllus as H. tirapensis (Biswas & Biswas, 2006) comb. nov. Detailed descriptions, photographs of copulatory organs and somatic characters, as well as a distributional map and an identification key to all Vietnamese species of Hyllus, are provided.